The Frontiers of Knowledge: Shouldn't the Other Speak her Own Language? - Figueira, Dorothy (Cadernos de Literatura Comparada, 2017)
Using the structuring metaphor of an imaginary meeting between Walt Whitman and Jose Marti, I examine the relationship between American formulations of World Literature and Comparative Literature and investigate how each discipline ‘welcomes’ the Other. I distinguish between what a European comparatist might envision about the relationship between the two disciplines, as working together in a symbiotic relationship to engage in passive and active canon reform. The European comparatist might take a neutral attitude to the recent American marketing of World Literature. I do not see this phenomenon in neutral terms and examine the American configuration of World Literature as a political program, discussing its origins in Area Studies, its relationship to the American academic model of multiculturalism and ultimately viewing it as a institutional strategy aiding in the management of diversity on US campuses.